Influencer Marketing in the Age of AI: Examining the Roles of Credibility, Content Quality, and Personalization in Shaping Trust, Emotional Attachment, and Purchase Intention in Pakistan - Siddique, Shaikh M Fakhre Alam; Naz, Iqra; Ali, Sehar (ACADEMIA International Journal for Social Sciences, 2025)
Influencer marketing has emerged as a powerful tool of digital persuasion; nevertheless, the processes according to which it affects consumer decision-making have not been explored well enough in the case of emerging markets where the institutional trust in online shopping is weak. The paper explores the influencer marketing effect on consumer purchase intention through analyzing the impact of influencer credibility, content quality, and artificial intelligence (AI)-driven personalization through the Pakistan social media environment. The study is based on the Source Credibility Theory and the Stimulus Organism Response (S-O-R) model and informed by attitude-based approaches as represented in the literature on consumer behavior and constructs an integrated model of both cognitive and affective influence pathways. The study utilized a quantitative, cross-sectional research design that involved the use of a structured survey in the sample comprised of active social media users in Pakistan and who have been recently exposed to influencer-endorsed content. There were 218 valid responses analyzed through the Partial Least Squares Structural Equation Modeling (PLS-SEM) that is appropriate in the context of theory expansion and the complicated models with mediation and moderation. According to the results, influencer credibility and AI-improved personalization have a significant positive effect on consumer trust and emotional attachment, and miscellaneous contents generally have a positive impact on purchase intention through a functional assessment and not relational bond. However, the most notable predictor of the purchase intention was consumer trust and the emotional attachment did not readily translate to the actual buying behavior. The consumer attitude portrayed a small yet significant moderating influence on the trust purchase intention relationship. The results emphasize the importance of trust-driven mechanisms over emotional persuasion in risk sensitive online space and give context specific insights into influencer marketing practices in new market.